PENGARUH KOMPETENSI KERJA DAN KEMAMPUAN KOMUNIKASI TERHADAP KESIAPAN KERJA SISWA JURUSAN BISNIS RITEL DI SMK SWASTA TELADAN PEMATANGSIANTAR T.A 2025/2026 - Putri Elisabet Marpaung; Benjamin Albert Simamora; Eduward Situmorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of work competency and communication skills on students' work readiness. This study used a quantitative approach with a causal associative method. The population consisted of 92 students, with a sample of 62 students selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The results showed that work competency had a positive and significant effect on work readiness, with a calculated t-value of 2.962, greater than the t-table value of 2.001, and a significance value of 0.004, less than 0.05. Communication skills had a positive and significant effect on work readiness, with a calculated t-value of 4.452, greater than the t-table value of 2.001, and a significance value of 0.000, less than 0.05. Simultaneously, work competency and communication skills had a significant effect on work readiness, with a calculated F-value of 56.384, greater than the F-table value of 3.153, and a significance value of 0.000, less than 0.05. The coefficient of determination value of 0.657 indicates that 65.7% of the variation in work readiness can be explained by the two variables. Communication skills have a more dominant influence than work competency.